Conceptions des futurs maîtres du primaire relativement à l'utlisation de la resolution de problèmes en mathématiques - Deblois, Lucie; Vezina, Nancy (Canadian Journal of Higher Education, 2001)
This article discusses the results of a study on preservice teachers's conceptions of a teaching activities included problem-solving. Four teaching activities on the concept of multiplication and division were proposed during a course. First, the preservice teachers were asked to identify the strengths and weaknesses. They were then invited to validate and justify their choice with expert subgroups according to cooperative learning strategies. Finally, they determined what should be retained for the learning and teaching of these mathematical notions. Analysis of the 88 questionnaires allowed us to study the conceptions of teaching activities used the problem-solving as a teaching strategy. It appears conceptions about these type of teaching activities. For example, preservice teachers viewed the illustration of a problem as the primary strength, but asking questions as a web to create confusion in pupils. When the mathematics content present no confusion, they can reflect more on the activities of pupils. The results help us to identify tension who will guide pedagogic intervention for the program.